Sistem Militer Sultan Muhammad Al-Fatih Dinasti Turki Utsmani - Suparman, Suparman (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2024)
The Ottoman Dynasty or better known as the Ottoman Turkish Sultanate was established from 1281 to 1924 AD. The era of Sultan Muhammad Al-Fatih who led from 1451–1481 AD was not only due to his quality as a leader who brought many changes to the Ottoman Turkish military system. Also because Sultan Muhammad Al-Fatih and his troops succeeded in conquering Constantinople and became the best leader and troops as mentioned by the Prophet Muhammad SAW. The purpose of this study is to describe the military policy of the Sultan Muhammad Al-Fatih era in 1451-1481 AD and to describe the military development of the Sultan Muhammad Al-Fatih era in 1451-1481 AD. In this article, the use of literature is prioritized, meaning that this article focuses on library research, because the analysis is directed at books and writings related to the discussion. The results of this study show that the organization of the Ottoman Turkish military system during the Sultan Muhammad Al-Fatih era was based on two things, namely internal and external factors. Internal factors such as the fact that he was a successor to the Ottoman Dynasty who was one of the great leaders of Islam whose piety, intelligence and personality were evident. Then external factors include his troops and weapons, both those that he maintained from the previous king's system and the innovations of Sultan Muhammad Al-Fatih. The military policies made by Sultan Muhammad Al-Fatih also included elements that paid attention to piety, welfare, togetherness, and the war skills of his troops. While the development of Sultan Muhammad Al-Fatih's military system included land and sea troops which were recognized by the world as one of the best troops ever